Antibodies for Assessing Circadian Clock Proteins in the Rodent Suprachiasmatic Nucleus - LeSauter, Joseph; Lambert, Christopher M.; Robotham, Margaret R.; Model, Zina; Silver, Rae; Weaver, David R. (PLOS ONE, 2012)
Research on the mechanisms underlying circadian rhythmicity and the response of brain and body clocks to environmental and physiological challenges requires assessing levels of circadian clock proteins. Too often, however, it is difficult to acquire antibodies that specifically and reliably label these proteins. Many of these antibodies also lack appropriate validation. The goal of this project was to generate and characterize antibodies against several circadian clock proteins. We examined mice and hamsters at peak and trough times of clock protein expression in the suprachiasmatic nucleus (SCN). In addition, we confirmed specificity by testing the antibodies on mice with targeted disruption of the relevant genes. Our results identify antibodies against PER1, PER2, BMAL1 and CLOCK that are useful for assessing circadian clock proteins in the SCN by immunocytochemistry.